DOI: 10.11606/t.11.2018.tde-20032018-105839
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do extrato da alga marinha <em>Ascophyllum nodosum</em> e do fosfito de potássio na morfofisiologia do fungo <em>Colletotrichum gloeosporioides</em>, na indução de resistência em mangas \'Tommy Atkins\' contra a antracnose e em características físicas e químicas desses frutos

Abstract: Pelo apoio incondicional, amor desmedido e por serem os melhores pais desse mundo! Aos meus irmãos, Alexandre de Melo e Fernanda de Melo Pelo amor que nos une, amizade e suporte ao longo de toda a minha vida! Ao meu avô (in memoriam), José Raimundo Anchieta Que partiu dizendo a todos, com o peito cheio de orgulho, que eu havia mudado para São Paulo só para fazer um curso. Estou de volta, vovô! O curso acabou! À minha avó, Rosa Maria Brito Que sempre esteve ao meu lado, em todas as decisões da minha vida! A Stê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
3

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 197 publications
1
3
0
3
Order By: Relevance
“…Means followed by the same letter do not differ according to the Scott-Knott test (p ≤ 0.05). The bars indicate the standard error of the mean.Source: Authors.The inhibitory effect of potassium phosphite on the in vitro growth of phytopathogens has also been observed in other studies Melo (2017). identified that 0.1% potassium phosphite 1in vitro development of Colletotrichum gloeosporioides isolated from 'Tommy Atkins' mangoes.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Means followed by the same letter do not differ according to the Scott-Knott test (p ≤ 0.05). The bars indicate the standard error of the mean.Source: Authors.The inhibitory effect of potassium phosphite on the in vitro growth of phytopathogens has also been observed in other studies Melo (2017). identified that 0.1% potassium phosphite 1in vitro development of Colletotrichum gloeosporioides isolated from 'Tommy Atkins' mangoes.…”
supporting
confidence: 66%
“…Roma 2013 The control of postharvest diseases using seaweed extract has also been reported in the literature. Melo (2017) evaluated the severity of anthracnose in mangoes treated with A.…”
Section: Evaluation Of the Alternative Products To Control Green Moldmentioning
confidence: 99%
See 1 more Smart Citation
“…Values were expressed as units of mg -1 chitinase protein, according to standard protein curve (Bradford, 1976). (Marx, 1969), plus the same doses of the A. nodosum extract used in the previous trials (Melo, 2017). For the induction of enzymes, the glucose of the medium was replaced by microcrystalline cellulose (1.0%) for the determination of exo-β-1,4-glucanase activity and, by carboxymethylcellulose (CMC) (1%), for the determination of the activity of endo-β-1,4-glucanase and β-glucosidase enzymes.…”
Section: Vasinfectummentioning
confidence: 99%
“…Dentre os produtos usados como controle alternativo de doenças de plantas, destacam-se os extratos de algas, que além de auxiliar no manejo de doenças ainda influenciam positivamente na produtividade (Carvalho & Castro, 2014). Ademais, embora poucos, é possível encontrar na literatura resultados promissores na utilização do extrato da alga Ascophyllum nodosum no manejo de doenças em pós-colheita (Gomes& Serra, 2013;Mafra, et al 2020;Melo, 2017;Ribeiro;Serra& Araújo, 2016).…”
Section: Introductionunclassified